2017
DOI: 10.1136/bmjopen-2017-017224
|View full text |Cite
|
Sign up to set email alerts
|

Use pattern and predictors of use of highly caffeinated energy drinks among South Korean adolescents: a study using the Health Belief Model

Abstract: ObjectivesConcerns about the use of highly caffeinated energy drinks among Korean adolescents remains. We compared adolescents’ perceptions regarding the use of drinks to their behaviours and factors.DesignA structured questionnaire based on the Health Belief Model was administered to 850 freshmen and sophomores at three high schools in Bucheon, South Korea. Benefits were defined as beneficial effects from the use of highly caffeinated energy drinks (eg, awakening from sleepiness) and harms as adverse effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…Consistent with previous studies in Australia [ 62 ] and elsewhere [ 9 , 25 , 32 , 44 , 67 , 70 ], we found regular energy drink consumption was significantly higher among males at 8%. This is unsurprising given marketing for these products is heavily directed towards males, such as through sports and video games [ 20 , 21 , 71 ], and the gender difference in consumption is also observed in adults [ 72 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies in Australia [ 62 ] and elsewhere [ 9 , 25 , 32 , 44 , 67 , 70 ], we found regular energy drink consumption was significantly higher among males at 8%. This is unsurprising given marketing for these products is heavily directed towards males, such as through sports and video games [ 20 , 21 , 71 ], and the gender difference in consumption is also observed in adults [ 72 ].…”
Section: Discussionsupporting
confidence: 92%
“…Raising adolescents’ awareness about the detrimental effects of energy drinks may also prove beneficial, with previous research finding that possessing such knowledge served as a barrier to consumption [ 9 , 20 , 70 ]. Currently among Australian adolescents there is a lack of awareness of energy drink ingredients and their actions [ 20 , 94 ], as well as confusion about serving size and recommended daily limit [ 20 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perceived barriers also exert an effect by means of perceived behavioral control, along with perceived benefits. This is consistent with the findings of a prior study [30] suggesting that the benefits and risks associated with health threats of adolescents' high caffeine intake were the strongest predictor variables. A prior study [30] found that high caffeine drinkers were less likely to recognize the severity and likelihood of the risks of excessive caffeine intake than non-drinkers.…”
Section: Chnrsupporting
confidence: 91%
“…Our results are in agreement with those of another previous study (Bulut et al, 2014) reporting that having a friend who consumes energy drinks (OR = 3.6, 95% CI = 2.6-5.0) was a factor affecting the energy drink intake of college students. In other previous studies (Ha et al, 2017;Kim et al, 2015), a positive awareness of energy drinks (OR = 2.75, 95% CI = 1.05-7.18) and the perception that the benefits outweigh the harms of consumption…”
Section: Discussionmentioning
confidence: 66%
“…Shift‐working nurses and prehospital emergency care personnel have a habit of consuming stimulant products such as caffeinated beverages (coffee and/or tea), energy drinks, and energy‐enhancing tablets to maintain arousal or enhance physical and mental performance (Pepłońska et al, 2019; Rooyen et al, 2021). There is a known tendency to consume energy drinks among individuals who have a low level of knowledge on energy drinks, who are oblivious to the risks of energy drinks, who do not perceive the threat of energy drinks to health, who perceive energy drink intake as highly beneficial, who perceive energy drink intake as having minimal harmful effects, and who least intend to discontinue energy drink intake (Ha et al, 2017; Mohammed et al, 2022; Subaiea et al, 2019).…”
Section: Introductionmentioning
confidence: 99%